Juventude e participação política: motivações, trajetórias e representações - Bertollo, Milena (2008)
This research attempted to identify and describe the trajectories of political participation of young affiliates of different political parties, as well as the associated meanings, motives, and representations. Eight young affiliates were interviewed, with ages ranging from 19 to 25 years, affiliated to a political party for at least one year. The data were collected by individual interviews, performed after a semi-structured script which included the topics: characterization of the participant, political engagement trajectory, reflections about youth and gender. The obtained information was submitted to the phenomenological method for psychological investigation and reorganized into narratives. The data pointed towards family, school, and church as important agents of political socialization. Personal disposition, the desire to make a difference in the world where they live, influence of the parents, and professional career were the main motivating factors for political insertion. With respect to reflections about youth and gender, the participants reproduce traditional social representation elements. The ambiguity with respect to representation of youth appears in the discourse of the interviewed youngsters. Albeit being represented as protesters and revolutionaries, youngsters are also seen as apathetic, hopeless, and alienated. A dynamics for identification and categorization was identified among the participants. On one hand, they share characteristics which identify themselves as a group (politically active youngsters), in opposition to the remaining youngsters (youngsters not interested in politics). On the other hand, there is also the internal dynamics of the group “politically active youngsters”, which happens in the differentiation between “right wing youngsters” and “left wing youngsters”. In this dynamics, the struggle between generations seem to unite youngsters, who point out the difficulty of occupation of spaces within the party, which is mainly led by adults. On gender relations, we find a certain mismatch between social representations and practices. Although the practice of political engagement is very similar among young men and women, the social representations indicate very conservative viewpoints. The generational condition, in this research, seems to be the most important basis where the young participants’ representations anchor.